INFLUENCE OF THE AT "WINGLETS" TYPE ON THE LONGITUDINAL STATIC STABILITY OF ANGLE OF ATTACK OF THE AIRCRAFT - Malikov E. Е.; Miltsov, V. E. (Science-based technologies, 2019)
The effect of the aerodynamic "AT winglets" wingtips on the longitudinal static stability of the aircraft is investigated by the method of equations of a steady straight-line horizontal flight. The aerodynamic forces created by the upper and lower parts of the wingtip "AT winglets" are defined. Assuming that the vertical projections of the pressure centers of all parts of the wingtips intersect the transverse axis, the dive and kicking moments of these forces are determined. The aerodynamic forces created by all four parts of the wingtip "AT winglets" are determined and their pitch moments are calculated. The vector of the total aerodynamic force of the wingtips is represented in the form of components along the associated coordinate system. Equilibrium equations for the steady motion of an aircraft with wingtips of the "AT winglets" type in a horizontal flight are recorded. This method is used to calculate the expression for the longitudinal moment coefficient of an aircraft in the presence of aerodynamic wingtips. The forward and backward arrangements of the centers of pressure of the tips with respect to the vertical plane passing through the lateral coordinate axis are considered. The derivatives of the coefficients of the roll and yaw moment coefficients for the slip angle for the wing with the tips that enter the equation for the lateral oscillation of the aircraft are determined. The correspondence between the derivatives of the coefficients of the moments of roll and yaw for the wings without the tips and with the tips for the slip angle is established. Using this correspondence, from the known differential equation of the lateral oscillation of an airplane with a wing without a wingtip, the corresponding equation of lateral oscillation of the airplane is obtained for the aircraft for a wing with a wing with wingtips. The expression of the longitudinal moment and its coefficient for an aircraft taking into account the influence of aerodynamic wing tips is derived. With small changes in the angle of attack, the partial derivatives of the longitudinal moment coefficient with respect to the angle of attack and the coefficient of lift are calculated. The conditions for the longitudinal static stab